Analysis of Fulfillment of the Principles of Justice and the Principle of Equality in Administrative Fines Provisions and Interest Rewards in the Tax Dispute Process - Satria Amiputra; Ning Rahayu (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Taxes are one source of state revenue derived from public participation. In Indonesia, the government in conducting tax collection will be in direct contact with the interests of the community. Implementation of tax collection in the middle of the community that is not in accordance with the balance of rights and obligations as well as tax laws will occur injustice for the taxpayer community, so that it can cause tax disputes between the taxpayer and the Director General of Taxes or the tax apparatus (tax authorities). Tax disputes between taxpayers and the Director General of Taxes or tax officials (tax authorities) are caused by differences in understanding of taxation provisions, differences in interpretation of taxation provisions, differences in viewpoints in evaluating facts, and may also be due to disagreements in the evidentiary process. This study aims to analyze the fulfillment of the principles of justice and equality in terms of administrative fines and interest rewards in the tax dispute process. This type of research is normative with a post positivism approach. The results of this study reveal that the rules regarding administrative sanctions in tax disputes as regulated in the 2007 KUP Law are unfair because taxpayers feel afraid to exercise or maintain their constitutional rights, so that the taxpayer's constitutional rights have been impaired when attempts to maintain their rights. Not fully the rules regarding administrative sanctions in tax disputes in accordance with the principle of equality or fairplay can be seen from Equality achieved only at the technical level and Equality not achieved at the substantive level.